Acoustic wave propagation simulation by reduced order modelling. Issue 3 (1st June 2018) - Basir, Hadi Mahdavi; Javaherian, Abdolrahim; Shomali, Zaher Hossein; Firouz-Abadi, Roohollah Dehghani; Gholamy, Shaban Ali
Abstract : Wave propagation simulation, as an essential part of many algorithms in seismic exploration, is associated with high computational cost. Reduced order modelling (ROM) is a known technique in many different applications that can reduce the computational cost of simulation by employing an approximation of the model parameters. ROM can be carried out using different algorithms. The method proposed in this work is based on using the most important mode shapes of the model, which can be computed by an efficient numerical method. The numerical accuracy and computational performance of the proposed method were investigated over a simple synthetic velocity model and a portion of the SEG/EAGE velocity model. Different boundary conditions were discussed, and among them the random boundary condition had higher performance for applications like reverse time migration (RTM). The capability of the proposed method for RTM was evaluated and confirmed by the synthetic velocity model of SEG/EAGE. The results showed that the proposed ROM method, compared with the conventional finite element method (FEM), can decrease the computational cost of wave propagation modelling for applications with many simulations like the reverse time migration. Depending on the number of simulations, the proposed method can increase the computational efficiency by several orders of magnitudes. Abstract : A reduced order modelling method is introduced for wave propagation modelling by using the mode shapes of the model. The numerical accuracy, computational performance and boundary conditions of the proposed method were investigated. According to the results, the proposed method substantially improves the computational efficiency of the reverse time migration.